Grantmanship for criminal justice and criminology - Davis, Mark S. (Mark Stephen), 1952- (SAGE, 1999)
This text directs the reader towards locating new sources of private funding as well as how to: formulate and state a problem that argues for funding, describe the methods for addressing the problem, detail and defend and budget and many others.